2021
DOI: 10.11591/ijece.v11i4.pp3003-3012
|View full text |Cite
|
Sign up to set email alerts
|

Improved control and monitor two different PLC using LabVIEW and NI-OPC server

Abstract: <span>This paper proposes an improved control and monitors between two different PLCs, the Mitsubishi, and Omron. The main advantage is interoperability and communication between both PLC. The use of NI OPC server as the software interface reached interoperability and communication. There were developed two field applications to test interoperability. Laboratory virtual instrument engineering workbench (LabVIEW) uses as the software application for creating the user interface to control and monitor. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…With respect to the use of a Siemes 1214C programmable logic controller, it allowed the control of actuators and sensors, guaranteeing the regulation and control of temperatures in the heat exchanger; In this regard, in [29] and [30], although they manage to perform temperature control in a heat exchanger of the same type, they mention that they do it using PID controllers; Rather than disagree regarding the type of approach used, from my perspective our proposals are not far from this because the Siemens 1214C programmable controller has a PID function block, which can also be used as a contingency or parallel alternative; However, the contribution is that it is being shown that both architectures are valid for the control of a heat exchanger. In relation to the acquisition and monitoring of data through the HMI interface, it was possible to perform the acquisition and monitoring of data in an optimal way; In this regard, in [33] he refers to the use of an HMI interface, specifying that it is convenient from the point of view of the historical record of alterations of the temperature variable under study, that this interface contains both graphic and numerical components; In this regard, we agree on this type of approach since what is sought through this interface is to have a representation of the behavior of the system, it will not necessarily be located in places close to the plant or process, so many times the HMI interface It is found in places distant from the process, so it must be strictly used to show information through graphics and its variations in real time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With respect to the use of a Siemes 1214C programmable logic controller, it allowed the control of actuators and sensors, guaranteeing the regulation and control of temperatures in the heat exchanger; In this regard, in [29] and [30], although they manage to perform temperature control in a heat exchanger of the same type, they mention that they do it using PID controllers; Rather than disagree regarding the type of approach used, from my perspective our proposals are not far from this because the Siemens 1214C programmable controller has a PID function block, which can also be used as a contingency or parallel alternative; However, the contribution is that it is being shown that both architectures are valid for the control of a heat exchanger. In relation to the acquisition and monitoring of data through the HMI interface, it was possible to perform the acquisition and monitoring of data in an optimal way; In this regard, in [33] he refers to the use of an HMI interface, specifying that it is convenient from the point of view of the historical record of alterations of the temperature variable under study, that this interface contains both graphic and numerical components; In this regard, we agree on this type of approach since what is sought through this interface is to have a representation of the behavior of the system, it will not necessarily be located in places close to the plant or process, so many times the HMI interface It is found in places distant from the process, so it must be strictly used to show information through graphics and its variations in real time.…”
Section: Discussionmentioning
confidence: 99%
“…Sánchez et al [32] it is described that it was possible to develop a neural network algorithm from the acquisition of data through a SCADA system from a heat exchanger system, evidence that the monitoring allowed to obtain the data permanently by monitoring the variables of the process (temperature), achieving a high performance of the neural network. In the same line of research [33] shows a predictive maintenance model is developed, which guarantees the optimal operation Indonesian J Elec Eng & Comp Sci ISSN: 2502-4752  Supervision, control and data acquisition system of a heat exchanger (Martín Díaz-Choque) 157 of a refrigeration system and temperature exchange in the process, from the integration of a SCADA system with sensors implemented through Arduino. Fareeza et al [34] the author points out that generating information through supervision and monitoring systems of an industrial process guarantees the flexibility of the system, since from these data the presence of some anomalies or failures can be foreseen as part of the process of some kind of disturbance, which will allow the parameters inherent to the industrial process to be corrected opportunely.…”
Section: Literary Reviewmentioning
confidence: 99%
“…The programming method used is the ladder diagram (LAD) method. The designing LAD can be running and verifying by a personal computer [25]. PLC takes the sensors signal and processed them by the program then gives the signal to the VFD which again processes this input signals and finally controlling the motor speed.…”
Section: Software Descriptionmentioning
confidence: 99%
“…Pada lembaga pendidikan khususnya pada laboratorium pendidikan vokasi, implementasi kontrol motor tiga fasa dengan PLC Siemens dalam modul forward reverse berbasis HMI LabView dan OPC sangat penting dalam dunia pendidikan, terutama di bidang teknik elektro [8], [9]. Dengan menggunakan modul forward reverse berbasis HMI LabView dan OPC, mahasiswa dapat mempelajari secara praktis bagaimana mengontrol motor tiga fasa dengan PLC Siemens, serta mengintegrasikan antara PLC dan HMI LabView menggunakan protokol OPC.…”
Section: Pendahuluanunclassified